Self Disclosure in Interpersonal Relationships : A Literature Study - Tria Fita Mei Linda; Meir Tasya Ilza Shafira; Rinjani Ayu Aistra; Indah Zuhriyatul Jannah (International Conference on Psychology and Education (ICPE), 2023)
This article aims to discuss more broadly about self-disclosure in interpersonal relationships using the literature study method. By using data obtained from credible secondary sources, such as books and journals that are no more than 10 years old, both published nationally and for international journals. Self-disclosure has an important role in interpersonal relationships. Effective disclosures contribute to greater intimacy, trust, and closeness in a relationship, so sharing personal information is a means of building and maintaining relationships. This research aims to investigate the extent of self-disclosure in interpersonal relationships. The method employed is a literature review, where researchers utilize previous studies as reference sources to support and reinforce the conducted research. The findings from this research indicate that self-disclosure can influence individuals in forming interpersonal relationships.